Pengaruh Kualitas Pelayanan, Kepercayaan, Risiko, Dan Teknologi Informasi Terhadap Penetrasi Pasar Keuangan Syariah Pada Bank BSI Area Langsa - Aqlima Geubrina; Hismendi Hismendi; Hilmi Hilmi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of service quality, trust, perceived risk, and information technology on the market penetration of Islamic finance at Bank Syariah Indonesia (BSI) Area Langsa. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to 270 active BSI customers in Langsa City who had experience using BSI banking services, including digital services.The results indicate that trust has a positive and significant effect on Islamic financial market penetration, with a path coefficient of 0.695 and a p-value of 0.000. Service quality also has a positive and significant effect, with a path coefficient of 0.159 and a p-value of 0.003. Information technology demonstrates a positive and significant effect, with a path coefficient of 0.316 and a p-value of 0.000. In contrast, perceived risk does not have a significant effect, with a path coefficient of 0.038 and a p-value of 0.383. The model explains 80.6% of the variance in Islamic financial market penetration (R² = 0.806), indicating strong explanatory power. Furthermore, information technology indirectly affects market penetration through trust, while mediation through service quality and risk is not significant.These findings suggest that enhancing customer trust, service quality, and digital technology adoption are crucial strategies for expanding the market penetration of Islamic finance. Therefore, BSI should continue strengthening customer confidence, enhancing service excellence, and optimizing information technology to expand its customer base and improve the competitiveness of Islamic banking services